Wnt5a is a crucial regulator of neurogenesis during cerebellum development - Subashini, Chandramohan (Sci Rep, 2017)
The role of Wnt5a has been extensively explored in various aspects of development but its role in cerebellar development remains elusive. Here, for the first time we unravel the expression pattern and functional significance of Wnt5a in cerebellar development using Wnt5a(−/−) and Nestin-Cre mediated conditional knockout mouse models. We demonstrate that loss of Wnt5a results in cerebellar hypoplasia and depletion of GABAergic and glutamatergic neurons. Besides, Purkinje cells of the mutants displayed stunted, poorly branched dendritic arbors. Furthermore, we show that the overall reduction is due to decreased radial glial and granule neuron progenitor cell proliferation. At molecular level we provide evidence for non-canonical mode of action of Wnt5a and its regulation over genes associated with progenitor proliferation. Altogether our findings imply that Wnt5a signaling is a crucial regulator of cerebellar development and would aid in better understanding of cerebellar disease pathogenesis caused due to deregulation of Wnt signaling.